Heterointerface construction for permalloy microparticles through the surface modification of bilayer metallic organic frameworks: Toward microwave absorption enhancement - Sun, Chang; Zhao, Kun-Yan; Huang, Ming-Lu; Luo, Cheng-Long; Chen, Xu-Dong; Wu, Hongjing; Wang, Ming (Journal of colloid and interface science, 2023)
[Display omitted] •MOF coating methods enhance microwave absorption property of permalloy.•Bimetallic MOFs have higher efficiency for improving microwave absorption.•The best coating bilayers are the inner Co/C layer and the outer Zn/C layer.•This special order of MOF bilayers can build more heterointerfaces.•Heterointerfaces give strong polarization effect and perfect impedance matching. Reasonable heterointerface modification can effectively regulate and enhance the microwave absorption of electromagnetic materials. The surface of magnetic permalloy (PM) microparticles is modified herein by coating double-layer metal organic frameworks (MOF), which are composed of a 2-methylimidazole cobalt salt (ZIF-67) layer and a 2-methylimidazole zinc salt (ZIF-8) layer. A stable heterointerface structure with cobalt/carbon (Co/C) and zinc/carbon (Zn/C) layers is formed on the surface of PM microparticles after pyrolysis. These particles include two types of composite particles of PM solely encapsulated by ZIF-67 or ZIF-8, PM@ZIF67 and PM@ZIF8, respectively, and two types of composite PM particles with a double-layered MOF outer shell structure obtained by exchanging the coating sequence (PM@ZIF8@ZIF67 and PM@ZIF67@ZIF8). Furthermore, the thermal decomposition temperature has a significant impact on the surface morphology and magnetic properties of the composite particles. After pyrolyzing at 500 °C, the PM@ZIF67@ZIF8 samples exhibit the highest microwave absorption performance among these samples. Specifically, the minimum reflection loss and effective absorption bandwidth of PM@ZIF67@ZIF8 after pyrolyzing at 500 °C can reach −47.3 dB at a matching thickness of 3.8 mm and 5.3 GHz at a matching thickness of 2.5 mm, respectively. A heterointerface with an electrical field orientation is created in the PM@ZIF67@ZIF8 particles, which effectively enhances the interface polarization and dipole polarization. Furthermore, the formation of a three-dimensional carbon network after pyrolysis is also useful for optimizing impedance matching and enhancing magneto-electric synergism.